2022
DOI: 10.1108/ijoa-06-2021-2802
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of cost, revenue and profit efficiency on bank performance: empirical evidence from Indian banking

Abstract: Purpose This paper aims to investigate the effects of cost, revenue and profit efficiency on bank profitability in an emerging economy such as India over the period 1997 to 2017. Additionally, this study examines the effect of efficiency on profitability across different ownership groups for a panel of 70 Indian commercial banks. Design/methodology/approach In the first stage, using stochastic frontier analysis, we estimate the efficiency scores of cost, revenue and profit over the examined period. In the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 103 publications
1
7
0
2
Order By: Relevance
“…The efficiency scores for the period running from 2009-10 to 2018-19 have revealed that of the three ownership groups of banks, the banks under foreign ownership are the most efficient ones (92.53%) in comparison to the private banks (90.20%) and public banks (86.04%). Bijoy (2022) has attempted to measure the impact of cost efficiency, revenue efficiency and profit efficiency on the profitability of Indian banks. Using Stochastic Frontier Analysis (SFA) and generalized methods of moments on the panel dataset of 70 Indian banks for the period spanning 1997-2017, the study has concluded that higher levels of cost, revenue and profit efficiency improve the profitability of Indian banks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The efficiency scores for the period running from 2009-10 to 2018-19 have revealed that of the three ownership groups of banks, the banks under foreign ownership are the most efficient ones (92.53%) in comparison to the private banks (90.20%) and public banks (86.04%). Bijoy (2022) has attempted to measure the impact of cost efficiency, revenue efficiency and profit efficiency on the profitability of Indian banks. Using Stochastic Frontier Analysis (SFA) and generalized methods of moments on the panel dataset of 70 Indian banks for the period spanning 1997-2017, the study has concluded that higher levels of cost, revenue and profit efficiency improve the profitability of Indian banks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bank overhead costs are simply incurred by banks indirectly related to efforts to get customers [2]. The use of technology can reduce certain overhead costs to increase profitability [4,13].…”
Section: Bank Overheadmentioning
confidence: 99%
“…Bank overhead costs are costs incurred indirectly in getting customers, namely the cost of labor and information technology used [5]. The use of information technology enables banks to reduce certain overhead costs as a form of cost efficiency [13]. Information technology contributes to the development of mobile telecommunication operators, internet service providers, computer hardware manufacturers, software developers, mobile device manufacturers, and software manufacturers, which help the banking sector to accelerate services [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with increased competitiveness, the banking sector in India has seen a process of bank consolidation, followed by mergers and acquisitions, resulting in a reduction in the number of competitors and an increase in bank concentration [ 38 ]. The major stream of commercial banking has dominated the Indian financial system.…”
Section: Theoretical Frameworkmentioning
confidence: 99%